COVID-19 and telehealth, education, and research adaptations (2020)
For decades, there have been government funded services to provide healthcare telephonically to remote sites both on the earth and in the air. This capability has evolved into what we now know as telehealth. The use of telehealth dramatically accelerated as a result of concerns for patient and healthcare provider safety during the SARS-CoV2 pandemic. Similarly, concerns regarding transmission of infection have required medical schools to provide robust, easily accessible virtual education options. At short notice, faculties have had to develop new telehealth focused curriculum components. However, telehealth, online education, and internet enabled research should not be simply a new way to do traditional jobs but rather, an opportunity to take advantage of how technology can best be used to develop new and better ways to provide care, educate health care providers, and support research.